MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE - DINDA QISTHINA GUPA (Departemen Matematika, 2021)
This literature study research aims to describe theoretically whether the cooperative learning of TTW type can enrich students’ understanding of mathematical notions. Literature study and observation are the data collection techniques employed in this research. The research data analysis did several things, namely (1) collecting literature then conducting a review of several essential terms in the study; (2) Perform journals analysis; (3) The discussion is carried out by linking the results attained from the journal investigation with existing theories; (4) Prepare assumptions constructed on the results of the analysis; (5) Making suggestions based on the findings obtained. Based on the results of the research and discussion, it was concluded that cooperative learning model of TTW can enhance students’ capability to recognize mathematical notions.Keywords- mathematical concept understanding, cooperative learning model, TTW